2017
DOI: 10.1088/1361-6463/aa59a8
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conduction across a boron nitride and SiO2interface

Abstract: The needs for efficient heat removal and superior thermal conduction in nano/micro devices have triggered tremendous studies in low-dimensional materials with high thermal conductivity. Hexagonal boron nitride (h-BN) is believed to be one of the candidates for thermal management and heat dissipation due to its novel physical properties, i.e. thermal conductor and electrical insulator. Here we reported interfacial thermal resistance between few-layer h-BN and its silicon oxide substrate using differential 3ω me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 33 publications
1
48
0
Order By: Relevance
“…Similarly, Yalon et al reported a lower value of ≈15 MW m −2 K −1 for MoS 2 with AlN and SiO 2 at room temperature, using Raman thermometry with laser‐induced heating. A comparatively higher conductance of 62.5 MW m −2 K −1 has been reported for metal‐coated single‐layer boron nitride on SiO 2 substrate via a 3ω technique . It was also shown that increasing the number of boron nitride layers (to a total thickness of 12.8 nm) led to a reduction of as much as ≈50% in the measured h K .…”
Section: Thermal Boundary Conductance Across Interfaces Composed Of 2supporting
confidence: 79%
See 2 more Smart Citations
“…Similarly, Yalon et al reported a lower value of ≈15 MW m −2 K −1 for MoS 2 with AlN and SiO 2 at room temperature, using Raman thermometry with laser‐induced heating. A comparatively higher conductance of 62.5 MW m −2 K −1 has been reported for metal‐coated single‐layer boron nitride on SiO 2 substrate via a 3ω technique . It was also shown that increasing the number of boron nitride layers (to a total thickness of 12.8 nm) led to a reduction of as much as ≈50% in the measured h K .…”
Section: Thermal Boundary Conductance Across Interfaces Composed Of 2supporting
confidence: 79%
“…A comparatively higher conductance of 62.5 MW m −2 K −1 has been reported for metal-coated single-layer boron nitride on SiO 2 substrate via a 3ω technique. [168] It was also shown that increasing the number of boron nitride layers (to a total thickness of 12.8 nm) led to a reduction of as much as ≈50% in the measured h K . [168] Tungsten diselenide on SiO 2 substrate showed similar thickness dependent behavior as reported by Behranginia et al [165] via an electronic-heating Raman-probe platform.…”
Section: Thermal Boundary Conductance Across Interfaces Composed Of 2mentioning
confidence: 94%
See 1 more Smart Citation
“…The TBC G=SiO 2 and TBC hÀBN=SiO2 values were previously reported for SLG [%83 (þ6.2/À5.5) MW m À2 K À1 ] [88] and monolayer h-BN [%63 (þ28/À15) MW m À2 K À1 ] [89] using the 3ω technique. Using these values, the resulting TBC Ti=G and TBC Ti=hÀBN are 48.5 (þ8.5/À14.3) and 73.3 (þ10.7/À2.9) MW m À2 K À1 , respectively.…”
Section: Resultsmentioning
confidence: 86%
“…Error bars were calculated using an MC method . G/SiO 2 and h‐BN/SiO 2 data taken from previous studies, respectively. Ti/G, Ti/h‐BN, and h‐BN/G TBC values estimated using series resistance approximation.…”
Section: Resultsmentioning
confidence: 99%